Peta Jalan (Road Map) dan Kebijakan Pengembangan Industri Gula Nasional (Forum Penelitian Agro Ekonomi, 2016)
EnglishThere are three major problems encountered by Indonesia in relation with sugar agribusiness. First, the declining sugar productivity, due among others to low on farm technology adoption and sugar factory efficiency. Second, the increasing sugar resulted from among others; the international prices of sugar that do not represent the true production efficiency because it is sold below its production cost; ad-hoc border measure policies; and many illegal sugar imports. Third, the unstable domestic prices of sugar because of inefficient distribution system. To overcome these problems, the future sugar industry development needs to be formulated into short-run development program (3 years), medium-run development program (10 years) and long-run development program (20 years). The short-run development program aims to rehabilitate the sugar factories in Java Island to enable them to produce crystal sugar with ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬Ãƒâ€¦Ã¢â‚¬Å“cost of good soldÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬Ãƒâ€šÃ‚Â being competitive with the international prices of sugar. The medium-run development program aims to develop the sugar factories outside Java through utilizing dry landÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬ÃƒÂ¢Ã¢â‚¬Å¾Ã‚Â¢s formerly allocated to transmigration now being no longer competitive for food crops development. The long-run development program aims to switch the ownership of sugar factory from the state enterprise to sugar cane farmers, and development of sugar cane based industry, such as ethanol, alcohol, etc. Moreover, it is also necessary to revitalize research and development activities through providing more sufficient funds.IndonesianAda tiga permasalahan utama yang dihadapi Indonesia berkaitan dengan agribisnis pergulaan. Pertama, produktivitas gula yang cenderung terus turun yang disebabkan antara lain karena penerapan teknologi on farm dan efisiensi pabrik gula yang rendah. Kedua, impor gula yang semakin meningkat. Hal ini disebabkan antara lain, karena harga gula di pasar internasional tidak menggambarkan tingkat efisiensi produksi yang sebenarnya, karena dijual di bawah ongkos produksinya; kebijakan border measure yang sifatnya ad-hoc; dan banyaknya impor gula illegal. Ketiga, harga gula di pasar domestik tidak stabil yang disebabkan oleh sistem distribusi yang kurang efisien. Untuk mengatasi permasalahan tersebut, maka pengembangan industri gula di masa yang akan datang perlu disusun dalam Program Jangka Pendek (3 tahun), Program Jangka Menengah (10 tahun) dan Program Jangka Panjang (20 tahun). Program jangka pendek ditujukan untuk melakukan rehabilitasi PG di Jawa, sehingga mampu menghasilkan gula hablur dengan harga pokok yang dapat bersaing dengan harga gula di pasar internasional. Program jangka menengah ditujukan untuk pengembangan PG di Luar Jawa, dengan memanfaatkan lahan kering eks transmigrasi yang kurang kompetitif bagi pengembangan tanaman pangan. Program jangka panjang ditujukan untuk pengalihan pemilikan PG BUMN kepada petani tebu, serta pengembangan industri berbasis tebu, seperti ethanol, alkohol, dan lain-lain. Selain itu, perlu juga dilakukan revitalisasi kegiatan research and development, dengan memberikan dukungan dana yang lebih memadai.
Keywords: sugarcane; sugar; productivity; import; price policies; industrial development; gula tebu; gula; produktivitas; impor; kebijakan harga; pengembangan industri